PENINGKATAN NILAI EKONOMI HASIL PESISIR PENDAMPINGAN PENGOLAHAN IKAN PINDANG DAN PENYULUHAN MENGENAI PENTINGNYA DIGITAL MARKETING SALAH SATU UMKM PINDANG DI DESA ADAT YEH GANGGA - Putu Cita Ayu; Gusti Ayu Agung Anik Pramiari Dewi; I Kadek Adi Kresna Cakra Wibawa; I Kadek Agus Widiatmika; I Kadek Deni Arta; Ida Ayu Arik Anggari Putri; Ni Made Tia Purnama Dewi; I Gede Aryana Mahayasa (UNHI Press, 2023)
Business is the key to the Indonesian economy, one of which is Micro, Small and Medium Enterprises, apart from is very wide distribution throughout Indonesia, it also because of its important position due to the large number of Indonesia resident in it. The number of UMKM in Indonesia is now vey arge and dominate as th front line of the economy in Indonesia. One of the UMKM in Yeh Gangga, Sudimara Village, Tabanan is the Pindang UMKM which manged by one of the local people, Mrs. Ni Wayan Sukawati or usually called Men Nurtiyani. This article was created to provide information about Pindang UMKM in Yeh Gangga, Sudimara Village, Tabanan. The research method we carried out was qualitative, using observation, method, interview method and training or practice methods. And the result of thi research sho that the problem faced by Mrs. Nurtiyani is that she has not been able to market her business throught out Tabanan or outside Tabanan. Or this reason, through this research, a mentoring program for indag production and this provision o promotional videos and digital marketing an be arried out to increase sales for Pindang Men Nurtiyani UMKM.